An Assessment of the Agenda between New Media and Traditional Mainstream Mass Media: A Comparative Analysis of Agendas: New Media vs. Traditional Mainstream Mass Media (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Social media and other online news sources, also known as the “new media”, have become an integral part of modern society. The presence of such new media, social media in particular, has threatened the existence of printed newspaper. The data indicate that a shift in consumer behavior has led more people to get their news and information online (New York Times, April 2009). However, the impact of the new media on print media is still manageable in India. This study aims to understand the impact of new media and print media on a representative subset of the Indian population.The research involves a thorough survey methodology and presents expert interviews to identify the preferred media for reading News. It also quantifies the social changes triggered by the advent of new media and user generated content. Our studies show that the drop in circulation of print media can be attributed to the younger sect of the Indian population, which prefers the interactive nature of the new media and the reduced latency with which they can access news.Mass media have always been constructing reality. Each media constructs different versions of reality which plays according to the tune of the media owners. With the rise of the new media, the reading public now has a different source of information about the existing realities. This study analyzes the different agendas of the new and traditional media. Four printed newspapers and four online newspapers were selected for this study. A content analysis of the different media was carried. The findings indicate that the different media projects different agenda. The constructed agenda reflect the prevailing philosophy the owners of these media.